The Problem of Fair Management in Politics: Religious Argument and Personal Interest Argument - Gokhan Mitroglou (Global Writing Academica Researching & Publishing, 2019)
This study analyzes politics tradition in Sunn political thought in terms of exploring the problem of just ruling. In the relevant literature, the dominant approach consi-ders Siyāsatnāmas as ethical advice in general and regards them as ineffective against an un-just ruler who has no ethical concern. This study criticizes this dominant view by claiming that in addition to the religous / ethical argument to promote a just rule, the Siyāsatnāma tradition develops a second argument designed specifically for an unjust ruler who ignores ethi-cal advice. This second argument is ignored by the dominant position about the Siyāsatnāma tradition. I have called it self-interest argument in this study. An unjust ruler 's self interest is to maintain, empower, and hand down his power to his descendants. The self-interest argu-ment tries to convince a ruler who dismisses ethical advice to adopt just ruling by revealing that even for an unjust ruler the best strategy is just ruling to reach for his worldly aims.